Management Issues in Emerging Information and Communication Technology (ICT) Driven Distance Education in Nigeria - M. O. Adeyeye; Oyeleke Oluniyi (West African Journal of Open and Flexible Learning)
Information and Communication Technology (ICT) driven distance education is gaining momentum in higher education in Nigeria. Likewise, the traditional face-to-face institutions are establishing a dual-mode form of instructional delivery system to drive some of their on-and-off campus programmes. The paper investigates the perception of stakeholders in two Nigerian universities; one dual-mode institution (Obafemi Awolowo University, Ile-Ife) and one open and distance institution (National Open University of Nigeria), on the best way open and distance education can be effectively managed with respect to funding, targeted audience, courses being offered, programme structure, technology adaptation, quality control and general administration. A descriptive survey method was adopted for the study. The sample consisted of 100 stakeholders drawn from the management, senior administrative staff and academic staff of the two institutions. A self-designed but validated questionnaire was used to obtain data from the respondents, and were analysed using simple percentage and Analysis of Variance (ANOVA) statistical methods. Findings showed that open and distance education was practicable and achievable in Nigeria, if it could be effectively managed. Also, findings showed that stakeholders had a relatively positive perception about the administration of ODL in Nigeria, not minding the teething challenges. In conclusion, to achieve a realistic ODE, the paper recommends the separation of ODL staff from the traditional university administrators, and also that a formal strategy of constant training for management staff and other staff should be instituted.